Characteristics of Water Distribution in Vadose Zone in the Soil Site and Its Impact on Site Preservation - ZHANG Xiaozhou; YUN Zhihan; YUAN Wei; LI Yi; ZHAO Fan (Renmin Zhujiang)
Affected by water,ruins of soil texture are prone to crack,crispness,salt accumulation,moss and other hazards,which is not conducive to their preservation.In order to find out the source of soil water damage in the soil site so as to provide a reliable basis for the preservation of this site,based on the refined hydrogeological survey,this paper used the Solinst Levelogger groundwater recorder and MW307GD-M4 wireless gradient soil three-parameter monitoring terminal to continuously monitor the water trend in vadose zone in a long time sequence,and analyse the cause and mechanism of water damage in the archeological shed.The results show that the moisture content of the vadose zone of the ruin is generally high,with that of the same layer outside the shed about 10% higher than that inside the shed,but the soil permeability coefficients mainly range from 2.07×10-5 to 3.41×10-5cm/s,suggesting the weak effect of the rainfall outside the shed on the soil in the shed through horizontal infiltration.The phreatic water level ranges from 3.2 to 5.6 m,with an amplitude of about 0.25 m within the hydrological year.The rising capillary water subject to its fluctuation can directly affect the excavation interface under extreme rainfall conditions as the main control factor of the water damage of the ruin of soil texture.By reference to the engineering-geological concept of “upstream flow interception,downstream flow discharge and local flow control”,regulating the moisture content of the soil body in the sacrificial area casts new light on the preservation of ruins of soil texture.